RISK BEHAVIORS RELATED TO SEXUAL PRACTICES IN ADOLESCENTS FROM PUBLIC SCHOOLS IN THE CITY OF RECIFE - Beserra, Maria Aparecida; Resende, Cristina Maria Mendes; Gregório, Vera Rejane do Nascimento; da Sena , Claudia Alves; Corrêa , Maria Suely Medeiros; Neta, Maria Joana Pereira; Spinelli, Maria Benita Alves da Silva; Low, Sandra Trindade (Seven Editora, 2024)
Introduction: The population of adolescents in the world is estimated at 1.3 billion, representing 16% of the world’s population. Adolescents have specific health needs related to their rapid physical, sexual, social, and emotional development and the specific roles they play in societies. Objectives to identify risk behavior in the sexual practices of adolescent students and correlate them with sociodemographic and behavioral variables. Method: This is a descriptive, cross-sectional and quantitative study. The sample consisted of 643 adolescents aged 12 to 18 years. Results: It was evident that (30.6%) of the adolescents had already had sexual intercourse, the first sexual intercourse occurred mainly in the age groups of 12 to 14 years (47.2%). In the subgroup that had sexual intercourse, (26.4%) had sexual intercourse with four or more partners. The percentage of condom use by adolescents and/or their partners in their last sexual intercourse was significant (69.0%), however, 30.0% of adolescents did not use condoms in their last sexual intercourse. Conclusions: There was an early onset of sexual activity, with a high frequency of partners, with exposure of adolescents to pregnancy and sexually transmitted diseases. DOI:https://doi.org/10.56238/sevened2024.037-080